2021
DOI: 10.1016/j.isci.2021.102394
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning predicts chromosomal instability from histopathology images

Abstract: Summary Chromosomal instability (CIN) is a hallmark of human cancer yet not readily testable for patients with cancer in routine clinical setting. In this study, we sought to explore whether CIN status can be predicted using ubiquitously available hematoxylin and eosin histology through a deep learning-based model. When applied to a cohort of 1,010 patients with breast cancer (Training set: n = 858, Test set: n = 152) from The Cancer Genome Atlas where 485 patients have high CIN status, our model ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Xu et al, developed a deep learning model to accurately classify chromosomal instability status on a cohort of 1010 patients with breast cancer (Training set: n = 858, Test set: n = 152) from The Cancer Genome Atlas achieving, an area under the curve of 0.822 with 81.2% sensitivity and 68.7% specificity in the test set. Patch-level predictions of chromosomal instability status suggested intra-tumor heterogeneity within slides [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al, developed a deep learning model to accurately classify chromosomal instability status on a cohort of 1010 patients with breast cancer (Training set: n = 858, Test set: n = 152) from The Cancer Genome Atlas achieving, an area under the curve of 0.822 with 81.2% sensitivity and 68.7% specificity in the test set. Patch-level predictions of chromosomal instability status suggested intra-tumor heterogeneity within slides [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the importance of CIN in breast cancer, it cannot be routinely detected in clinic due to technical shortcomings ( 24 ). Although most studies still detect CIN by traditional detection methods, such as comparative genomic hybridization (CGH), single nucleotide polymorphism (SNP) array, polymerase chain reaction (PCR), and flow cytometry, these methods are not excessively accurate.…”
Section: Methods Of Chromosomal Instability Detectionmentioning
confidence: 99%
“…The delta-radiomics is proposed as a biomarker to help in predicting cancer treatment outcomes [ 81 ]. Some recent studies reported that ML predicts somatic mutation and chromosomal instability of tumors from images [ 82 , 83 ]. Thus, ML is expected to become more and more important as the development of multimodal characterization of tumor cells continues.…”
Section: Machine Learning—a Keystone That Paves the Way For Precision Oncologymentioning
confidence: 99%